SIMULASI GELOMBANG AIR DANGKAL UNTUK PEMBANGKIT ENERGI OSCILLATING WATER COLUMN - KURNIAWAN, EKA ANDHIKA; ADITSANIA, ANNISA; GUNAWAN, P. H. (E-Jurnal Matematika; Vol 7 No 1 (2018)DO - 10.24843/MTK.2018.v07.i01.p180, 2018)
Development of human causes the increasing of the demand of energy for living. Sea wave energy is one of the alternative energy sources which is renewable and sustainable, no impact on environmental pollution. The goal of this paper is to simulate the level of water wave using shallow water equation for generating energy oscillating water column. The solution of the equation is approximated using LaxFriedrich scheme and will be compared with the analytic solution in standing wave problem. Simulation is used to obtain the results of the energy in the form of electrical power generated by ocean wave. The results of the error of numerical validation is obtained 0.32%. Moreover, the results of the potential energy depend on the height of the surface waves is found 1574.46 Watts the average of water level is 0.881 meters.